The Development of Modern Art in Mongolia: On the Example of Mongolian Modern Painting of the Late Twentieth and Early Twenty-First Centuries - Selenge Tumur-ochir (Publishing house "Sreda", 2021)
Modern art in Mongolia has been developing since the last century. The art appeared as a result of artists' ideas, expression of national mentality and other factors. As some researches said: "Mite of the abstract paintings were established in Hun states, because when this times, all of the people to the paint-ed effect of their mind on the rock of cave" on their tractate book. That says that the abstract paintings was established at that time, but according to other sources it was developed in 1960. For example, in 1968 Mongolian young painters orga-nized an exhibition named: the first exhibition of young painters. Then, in 1980 modern and contemporary arts started developing. The purpose of the study is to analyze the development and classification of modern art in the late twentieth and early twenty-first centuries, which are kept in art galleries. The study was con-ducted in the following steps: to study modern Mongolian art and to identify cur-rent trends in its evolution. The study classified 2,333 paintings. Consequently the next conclusions were drawn: abstractionism, post-impressionism, and im-pressionism were more developed in modern paintings created in 1990-2000. Modern paintings created in 2000-2009, on the other hand, were more developed in abstraction, fauvism, surrealism, and symbolism. This shows that modern Mongolian artists prefer abstract and symbolic paintings. Before 1990, there was a lot of realism, but since 1990, modernism has developed a lot and has become a major trend.